2021
DOI: 10.1038/s41398-021-01488-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing prediction of response to antidepressant medications using machine learning and integrated genetic, clinical, and demographic data

Abstract: Major depressive disorder (MDD) is complex and multifactorial, posing a major challenge of tailoring the optimal medication for each patient. Current practice for MDD treatment mainly relies on trial and error, with an estimated 42–53% response rates for antidepressant use. Here, we sought to generate an accurate predictor of response to a panel of antidepressants and optimize treatment selection using a data-driven approach analyzing combinations of genetic, clinical, and demographic factors. We analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 74 publications
2
35
0
Order By: Relevance
“…Taliaz et al also completed additional statistical calculations of the models performance. The sensitivity, specificity, positive predictive value and negative predictive value were 68.7%, 71.4%, 71.7% and 69%, respectively [ 113 ]. In comparison after only 2 reviews, our recall rate (also known as sensitivity) was 71.4%, similar to Taliaz et al, results and our precision rate (also known as positive predictive value) was 97.4% which far exceeded Taliaz et al, results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taliaz et al also completed additional statistical calculations of the models performance. The sensitivity, specificity, positive predictive value and negative predictive value were 68.7%, 71.4%, 71.7% and 69%, respectively [ 113 ]. In comparison after only 2 reviews, our recall rate (also known as sensitivity) was 71.4%, similar to Taliaz et al, results and our precision rate (also known as positive predictive value) was 97.4% which far exceeded Taliaz et al, results.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, de Nijs et al were able to create individualised models to predict 3- and 6-year symptomatic and global outcomes of patients with schizophrenia-spectrum disorders (mainly with established illness, but variable illness duration) based on patient-reportable data with a study size of 523 schizophrenia-spectrum patients [ 112 ]. Also in 2021, Taliaz et al used genetic, clinical and demographic data from patients with solely MDD in the STAR*D Report to create an ML algorithm that generated an accurate predictor of response to three antidepressant medications with an average balanced accuracy of 72.3% and 70.1% across the medications in validation and test sets, respectively [ 113 ]. They then obtained data from the Pharmacogenomic Research Network Antidepressant Medication Pharmacogenomic Study (PGRN-AMPS) of patients treated with citalopram (a selective serotonin reuptake inhibitor) [ 113 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three large genome-wide association studies (GENDEP [ 11 ], STAR*D [ 12 ], and MARS [ 13 ]) have demonstrated an association between genetic variants across the whole genome and the effectiveness of antidepressants, but the small effect size involved in the antidepressant effect limits the clinical application of genetic biomarkers [ 14 ]. Taken together, although there are some known predictors associated with MDD and with the treatment response to antidepressants, establishing a predictive model is necessary to tailor the treatment outcomes of individual MDD patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%